(untitled) (Annals of Medical Research, 2021)
Aim: Migraine headaches are one of the serious complaints of patients seeking emergency department (ED) with symptoms of many health problems. In this study, we aimed to examine predictive values of hematological parameters on chronic migraine.Material and Methods: The files of patients admitted to ED of Ufuk University Hospital between January 2016 and November 2016 with a headache and who underwent hematological analyses at emergency admission were analyzed retrospectively. After exclusion criteria were applied, 55 patients with migraine attacks who were previously diagnosed with migraine by a neurologist included in this study.Results: There was not a statistically significant difference between age and sex distribution of groups (p>0.05), whereas a statistically significant difference was found for family history between patient and control groups (p0.05). Attack frequency was above 3 in most patients (74.5%), and mean migraine duration was 9.00±9.49 years. Red blood cell count (RBC), hemoglobin and hematocrit levels of patient groups were significantly higher than the control groups (p0.05). Receiver operating characteristic (ROC) analysis showed that hematocrit was the most important parameter for migraine, followed by RBC and hemoglobin. In binary logistic regression analysis, high hematocrit level is an effective factor for migraine with controlled multi-parameter regression analysis (OR=0.601; p0.05).Conclusion: The results of this study show that hematocrit levels of patients can be used to predict or distinguish migraine attack in ED in order to provide fast and correct treatment. Keywords: Migraine; pain; headache; hematocrit; emergency.